If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -5z + -7 = -42 Reorder the terms: -7 + -5z = -42 Solving -7 + -5z = -42 Solving for variable 'z'. Move all terms containing z to the left, all other terms to the right. Add '7' to each side of the equation. -7 + 7 + -5z = -42 + 7 Combine like terms: -7 + 7 = 0 0 + -5z = -42 + 7 -5z = -42 + 7 Combine like terms: -42 + 7 = -35 -5z = -35 Divide each side by '-5'. z = 7 Simplifying z = 7
| 3/8x-5/7 | | f(x)=2/5x-4 | | 15x^2-10x-3x^2+8+11x= | | 2x^5+4=0 | | 2346x=55*2 | | 25y+3=8 | | 4+5+5=450 | | 2k(-3k+4)+6(k^2+10)=k(4k+8)-2k(2k*5) | | 2/5x-2=4 | | 2x-6-3i=10-3yi | | -0.5x+7.68=-0.7x+1.68 | | (4x-1)+6i=2+(5y+2)i | | 6r^/12r | | 32+8=52 | | 4x+12-3x+7=x+4 | | y-(-6)=1/3(x-(-2)) | | -0.5+7.68=-0.7x+1.68 | | 4x^2-3x+9=8x+2 | | 4+11x=-26+x | | 5x+8+3x-x+4=6x-3 | | 22+7=30 | | 4.2(4+3x)-4.8=12 | | 3x-1/2= | | -x^4-3=4 | | t^2-5t-50=0 | | t^2+3t-70=0 | | 4(5m-n)+5(n-m+3)= | | 1.3+0.4x=0.5 | | 5x+1=14x+2 | | 6(x+4)+3=6x+2 | | f=5+4x-x^2 | | (1/16)^3/2 |